The Role of School Heads in Efforts to Build the Character of Participants Students in the First School of State 1 Talang Ubi - Rumiyah, Rumiyah; Fitria, Happy; Wahidy, Achmad (Jurnal Pendidikan Tambusai, 2021)
This study aims to determine the implementation of the vision and mission, the principal in an effort to build the religious character and discipline of students, at SMPN 1 Talang Ubi Penukal Abab Lematang. Ilir. The method used in this research is a qualitative method. The data collection instruments used were interviews, observation, and documentation. The results of this research. First, the implementation of the vision and mission of the Principal of SMPN 1 Talang Ubi in building religious character and discipline of students is to make the character of noble character become character and culture in their daily lives, the two principals in building the character of students through exemplary, reprimand, motivation, environmental conditioning, habituation, and character integration through learning activities. Third, the supervision carried out by the principal in building the character of students includes monitoring teachers in carrying out character learning in class, overseeing the course of character education program activities, checking the condition and integrity of school facilities and evaluating through briefings and meetings about character education programs.